Rethinking Sociology from an Islamic Jurisprudential Perspective - Busari, Saheed Abdullahi (University of Lagos Press, 2021)
Islamic Jurisprudence is a branch of Islamic revealed knowledge with several dimensions such as the sources of Islamic legal theories, Maqāsid al-Shariah, the Islamic legal maxims and other Islamic fundamental principles. Contemporary Islamic scholars have argued that the principles of Islamic jurisprudence encapsulate significant paradigms of sociology. This claim has attracted the attention of sociologists, researchers and scholars in the humanities on the dire need to ascertain the synergy between Islamic jurisprudence and sociology. This study aims to explicate the significance of Integration of knowledge and the convergence between Islamic jurisprudence and sociology. Doing so, this paper aims to employ the doctrinal methodology of reviewing library literature to articulate overlap between sociology and Islamic jurisprudence. The study will explore the threshold of Islamic jurisprudence, sociology and further analyse the focal integrals dimensions in their concepts, theories, principles and methodologies. This study also proposes a holistic and applicable rethinking into the dimensions of sociology from an Islamic Jurisprudential perspective.